Upaya Kementrian Perdagangan dalam Bernegosiasi melalui Instagram terhadap Kenaikan Harga Minyak Goreng bagi Konsumen - Prayogi Adie Pradja (KOMVERSAL, 2022)
ABSTRACT This study aims to determine consumers who still consume cooking oil. The research method that the researcher has done is using a quantitative method. The population in this study are consumers in Indonesia. Analysis and data collection was done by filling out a questionnaire via google. The results of this study stated that as many as 89.8% of 59 respondents stated that it was very influential that the increase in cooking oil prices was very influential in daily life for consumers, as many as 86.4% of 59 respondents stated that it was very helpful that the efforts of the ministry of trade regarding policy one price of Rp.14,000 per liter of cooking oil, 64.4% of 59 respondents said it was very appropriate in the government's efforts to handle the increase in cooking oil prices, as many as 55.9% of 59 respondents said it was very appropriate regarding the efforts of the ministry of trade to carry out negotiations and communication through social media Instagram.